2022
DOI: 10.1007/s11205-022-02884-y
|View full text |Cite
|
Sign up to set email alerts
|

Experienced Well-Being and Labor Market Status: The Role of Pleasure and Meaning

Abstract: This paper examines the experienced well-being of employed and unemployed workers. We use the survey-adapted Day Reconstruction Method of the Innovation Sample of the German Socio-Economic Panel Study to analyze the role of the employment status for well-being, incorporating time use. We use the novel P-index to summarize the average share of pleasurable minutes on a day and show that in contrast to evaluative life satisfaction the unemployed experiences more pleasurable minutes due to the absence of working e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Several DRM studies did not find any differences between employed and unemployed individuals in terms of time-weighted measures of AWB, which has often been explained by an interplay between the saddening effect and the time composition effect (Dolan et al, 2017;. Other DRM studies suggested that unemployed individuals are significantly sadder, more often in pain, experience similar levels of happiness, stress, and tiredness (Krueger & Mueller, 2012) and have higher levels of enjoyment (Hoang & Knabe, 2021;Wolf et al, 2019) compared to employed individuals. Overall, the extant evidence from studies that are less prone to recall bias does not confirm negative effects of unemployment on AWB.…”
Section: Effects Of Unemployment On Affective Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several DRM studies did not find any differences between employed and unemployed individuals in terms of time-weighted measures of AWB, which has often been explained by an interplay between the saddening effect and the time composition effect (Dolan et al, 2017;. Other DRM studies suggested that unemployed individuals are significantly sadder, more often in pain, experience similar levels of happiness, stress, and tiredness (Krueger & Mueller, 2012) and have higher levels of enjoyment (Hoang & Knabe, 2021;Wolf et al, 2019) compared to employed individuals. Overall, the extant evidence from studies that are less prone to recall bias does not confirm negative effects of unemployment on AWB.…”
Section: Effects Of Unemployment On Affective Well-beingmentioning
confidence: 99%
“…Further, having a meaningful job was found to be negatively correlated with intentions to retire and absenteeism (Nikolova & Cnossen, 2020). DRM data indicated that being at work provides individuals with higher levels of meaning compared to many other activities even if it is not perceived as pleasurable (White & Dolan, 2009; Wolf et al, 2019). More evidence for the importance of EWB in the context of employment comes from an extensive case study by Synard and Gazzola (2017) who studied 20 Canadians who had involuntarily lost their jobs in the technology sector between 2000 and 2006.…”
Section: Effects Of Unemployment On Cognitive Well-beingmentioning
confidence: 99%
“…Previous studies indicate that health and income are significantly related to experienced well-being (Killingsworth, 2021; Miret et al , 2017; Wolf et al , 2019). Recent COVID impact studies suggest that the loss of income, unemployment and increasing COVID health concerns have a profound impact on experienced well-being of tourism employees (Carnevale and Hatak, 2020; Mcguire et al ., 2021; Ozdemir, 2020) and their consumption sentiments and habits (Martin et al , 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the one hand, the unemployed experience lower levels of well-being than the employed when engaged in the same kind of activities Krueger and Mueller 2012). On the other hand, employed persons rate working among the least pleasant activities during their days (Kahneman et al 2004;White and Dolan 2009;Bryson and MacKerron 2017;Hoang and Knabe 2021a;Wolf et al 2022). Since, by definition, the employed have to spend more time working than the unemployed, this worsens their average emotional experience over the course of the day.…”
Section: Introductionmentioning
confidence: 99%
“…The two effects work in opposite directions, such that it is not clear, a priori, which of the two groups feels better over the entire day. Various studies find that the saddening and time-composition effects offset each other, such that unemployment is not negatively related to day-average experienced wellbeing and Wolf et al (2022) for Germany, Flèche and Smith (2017) for France, and Hoang and Knabe (2021a) for the UK). For the United States, Krueger and Mueller (2012) find that the saddening effect dominates when looking at the specific feelings of sadness and pain, while Dolan et al (2017) do not find differences between aggregate emotional well-being measures of the employed and the unemployed.…”
Section: Introductionmentioning
confidence: 99%